Use of Soil Ameliorant And Inorganic Fertilizer to Increase Soil Fertility Phosphorous Concentrations in Plant Tissue, Growth and Yield of Shallot in Dry Land - Mulyati Mulyati; A.L Sania; J Priyono; A.B Baharuddin; R.S Tejowulani (Postgraduate, University of Mataram, 2022)
Sub-optimal land use including dry land in West Nusa Tenggara (NTB) has not been optimal due to various land biophysical constraints such as low soil fertility, physical conditions with rough soil texture, and uncertain water availability, so efforts are needed to improve the land condition. . Shallots (Allium ascalonicum L.) is one of the vegetables that have a high enough potential to be developed in the land. The purpose of this study was to determine the interaction of various soil enhancers and doses of inorganic fertilizers on growth, tuber yield, and P content of shallot plants in suboptimal land. The method used in this research is the experimental method. The experimental design used was a Randomized Block Design which was arranged in a factorial design consisting of two factors. The first factor is a soil amendment, consisting of 4 types, namely: P0= without soil ameliorant; P1= 20 tons ha-1 manure; P2= 5 tons ha-1 biochar; P3= 10 tons ha-1 mushroom baglog waste. The second factor was the dose of NPK fertilizer, consisting of N1=150 kg ha-1; N2 = 300 kg ha-1; N3=450 kg ha-1. Each treatment combination was repeated 3 times. The results showed that there was an interaction between soil amendments and the dose of NPK fertilizer on organic C and soil CEC. But there was no interaction between the growth and yield of shallot bulbs. Soil ameliorant and dose of NPK fertilizer alone affected growth, namely the height and number of leaves of shallot plants. The best treatment for tuber yield was obtained in a combination of an application of 20 tons ha-1 of manure and 450 kg ha-1 of NPK fertilizer. Likewise with the P concentration in the onion plant tissue.